1998
DOI: 10.1162/089892998562690
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Brain Potentials and Case Information in Syntactic Ambiguities

Abstract: Abstract• In an ERP stud\', German sentences were investigated that contain a case-ambiguous ;\IP that mav be assigned accusative or dative case. Sentences were disambiguated by the "erb in final position of the sentence. As our data show. sentences ending in a verb that assigns dative case to the ambiguous NP elicit a clear garden-path effect The garden-path effect was indicated by a broad centro-posterior negative shift that occurred between 300 and 900 msec after the dative-assigning verb was presented.~o e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 43 publications
5
38
0
Order By: Relevance
“…Previous research in German has indicated that disruption and/or reanalysis of thematic role assignment in on-line sentence processing also elicits an N400 response. An N400 is elicited when noun phrases are ambiguously case-marked, such that thematic role assignment cannot take place until sentence end in verb-final clauses (Hopf, Bayer, Bader & Meng, 1998;Bornkessel, McElree, Schlesewsky, & Friederici, 2004), and an N400 + P600 complex is elicited when two animate noun phrases in the same clause illicitly receive the same case marking, such that thematic role assignment becomes impossible (Frisch & Schlesewsky, 2001.…”
Section: Disruption Of Thematic Role Assignment: N400 Effects?mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research in German has indicated that disruption and/or reanalysis of thematic role assignment in on-line sentence processing also elicits an N400 response. An N400 is elicited when noun phrases are ambiguously case-marked, such that thematic role assignment cannot take place until sentence end in verb-final clauses (Hopf, Bayer, Bader & Meng, 1998;Bornkessel, McElree, Schlesewsky, & Friederici, 2004), and an N400 + P600 complex is elicited when two animate noun phrases in the same clause illicitly receive the same case marking, such that thematic role assignment becomes impossible (Frisch & Schlesewsky, 2001.…”
Section: Disruption Of Thematic Role Assignment: N400 Effects?mentioning
confidence: 99%
“…The first two of these difficulties applied ceteris paribus to the German studies that used ambiguous case marking to obscure thematic relations (Hopf, Bayer, Bader & Meng, 1998;Bornkessel, McElree, Schlesewsky, & Friederici, 2004), and all three applied to the German studies that used illicit duplicate case marking to impede successful thematic role assignment (Frisch & Schlesewsky, 2001. It is thus reasonable to expect that these same three disruptions of thematic processing will conspire to elicit an N400 response when English language materials are used, even though English does not overtly case-mark its noun phrases (except of course for pronouns).…”
Section: Disruption Of Thematic Role Assignment: N400 Effects?mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been only a few reports on N400-like effects elicited by syntactic anomalies (see, e.g., Osterhout & Holcomb, 1992;Osterhout, Holcomb, & Swinney, 1994). However, some of these anomalies involved subcategorization violations for which an additional lexical reaccess can be assumed (Frisch & Friederici, 1998;Hopf, Bayer, Bader, & Meng, 1998). Or, the negativity occurred at the final word of a word string, which could be interpreted as an incomplete sentence (e.g., The broker persuaded to sell the STOCK.…”
Section: Notesmentioning
confidence: 99%
“…Experimental studies by Hopf, Bayer, Bader & Meng (1998) and Bader & Bayer (2006) have established that the HU-MAN SENTENCE PROCESSING MECHANISM (HSPM) has an on-line prefererence for assigning accusative (structural) Case to a Case-ambiguous NP/DP whereas dative (lexical) Case is dispreferred. Given that lexical Case in general has to be expressed morphologically, the proposal by Bayer, Bader & Meng (2001) has been that DPs with lexical Case require an extra shell which Bayer et al (2001) dubbed KP -cf.…”
Section: Evidence From Sentence Processingmentioning
confidence: 99%